ESL learners' usage of grammatical morphemes : the case of IIUM students - Ahmed, Abdel Rahman Salih (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 1998)
English language teaching and learning in ESL/EFL situation reflect a wide variety of difficulties learners normally encounter especially when they deal with grammar. Despite being instructed and majoring in English, and despite having exposure to be target languate, the learners' language is still characterized by considerable grammatial errors. By following the procedure of Error Analysis model (1981). this study analyses the aspects and origins of the difficulties relating to the use of the grammatial -s morpheme in the written English of ESL learners of I.I.U.M. The study designed three tests as tools for collecting data. These tests were conducted to stimulate the subjects' actual use of the -s morpheme items. The study arrvied at many interesting findings. First, the subjects' errors showed variation in terms of patterns. Second, omission errors appeared to be the most common error type among the learners. Third, there is no evidence of acquirng certain linguistic features in sequential order. Last but not least, the subjects' errors have valuable significance in understanding the psycholinguistic aspects of the process of target language learning. Moreover, giving much attention to the types and causes of learners' errors would facilitate providing authentic and valid pedagogical solutions. Various factors are specified in explaining the erros.